After innocence : visions of the Fall in modern literature - Otten, Terry (University of Pittsburgh Press, 1982)
The fear of falling, the awareness of lost innocence, lostillusions, lost hopes and intentions, of civilization indecline-these are the themes which link literature to theology,both concerned with the shape of human destiny. Otten discusses thecontinuing viability of the myth of the Fall in literature. Herelates a wide variety of romantic and modern works to fundamentalissues in modern Christianity. .
Keywords: Fall of man in literature.; Literature, Modern -- 19th century -- History and criticism.; Literature, Modern -- 20th century -- History and criticism.; Chute de l'homme dans la littérature.; Littérature -- 19e siècle -- Histoire et critique.; Littérature -- 20e siècle -- Histoire et critique.; LITERARY CRITICISM / General; Fall of man in literature; Literature, Modern; 1800-1999; Criticism, interpretation, etc.